Association of Etiological and Pathological Features of Brain Abscess with Outcome - Mushtaq Ahmad Mian1, Saleem Abbasi, Fazal Amin Khan ,Muhammad Usman (Journal of Rawalpindi Medical College, 2017)
To study the etiological and pathological factors of brain abscess and to relate with the final outcome. Methods: In this observational study patients with brain abscess were observed in detail with the clinical profile, etiology, microbiology and their final outcome after one year.Chi-square test was applied to associate etiological and pathological factors with management outcome. Results: The majority of patients were in their 2nd and 3rd decade of life with two third proportion comprising of males. The most frequent etiological factor was chronic suppurative otitis media (CSOM) ( 55%),followed by head injury (12% ) and congenital heart disease (10%). Microbiological data revealed 16% streptococci, 10% staph. aureus, 7% staph. epidermidis and 5% proteus as major pathogens in the study patients. Head injury and CSOM were found associated with death and morbidity in this study. Conclusion: Brain abscess has multi dimensional causes. CSOM and head injury were found associated with death and severe morbidity as hemiparesis and fits. CT findings and microbiological data were not associated with outcome.